Efficacy of Carumcarvi L. (Caraway), Eculaptuscamaldulensisdehnh (Red Gum) Andnigella Sativa (Black Seed) Against Greater Wax Mothgalleria Mellonellal.Innaeus (Lepidoptera:Pyralidae) - Abass Hussien, Wegdan; Mahammed Khaeir, Siefaldinn; Haroun Mohamed Adam, Abubaker; El bagi Elsayed Ali, Abd (Journal of Agronomy Research, 2022)
The greater wax moth considered one of the most worldwide-spread pests of the bee wax. This Study was designed to investigate the insecticidal activity of Carumcarvi, Eculaptus camaldulensis and Nigella sativa against 3rd larval instar of G.mellonellathrough laboratory screening. Five concentrations (5%, 7.5%, 10%, 12.5% and 15%) of each plant extract were used in this experiment. Mortality (%) was recorded after 24, 48, 72 and 96 hrs post treatment. The results showed C. carvi, E. camaldulensis and N.sativahave insecticidal activity against 3rd_ instar larvae of G. mellonella. The highest concentration (15%) caused 90% ,86.7% and 80% larval mortality after 96 hrs for C. carvi,E. camaldulensis and N.sativarespectively. The statistical analysis revealed that there is a significant difference (p< .001) between all treatments and control. The results also clearly demonstrate that the C. carvi are significantly more toxic than E. camaldulensis and N. sativa, whereas the LC50 values were 5.4% forC. carvi,6.0% for E. camaldulensis and 6.2% for N. sativa.
Keywords: Insecticidal activity; Mortality; Larval instar; Investigate; Toxic